2021
DOI: 10.1021/acs.jpcc.1c06587
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Surface Phase Transitions in Multiferroic BiFeO3 Nanocrystals Probed via Electron Paramagnetic Resonance

Abstract: The low-temperature phase transitions observed in magnetoelectric bismuth ferrite (BiFeO 3 , BFO) have recently been a topic of interest to several researchers. This communication focuses on connecting recent structural revelations, such as the existence of a "skin" layer in BFO, the lattice contraction, and subsequent expansions in the skin layers with X-band electron paramagnetic resonance (EPR) spectra. A closer look at Lande's g-factor and the EPR asymmetry parameters reveal vital information about the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Because BFO is insulating while SRO is metallic, the transport property should be dominated by the SRO layer. We suppose that interlayer coupling between the two materials resulted in the observed anomaly, whose origin is the spin state change in the BFO layer [ 22 ]. Slight resistivity upturn below 20 K may be attributed to the localization effect due to disorder [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because BFO is insulating while SRO is metallic, the transport property should be dominated by the SRO layer. We suppose that interlayer coupling between the two materials resulted in the observed anomaly, whose origin is the spin state change in the BFO layer [ 22 ]. Slight resistivity upturn below 20 K may be attributed to the localization effect due to disorder [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The magnetization confirms that the superlattice sample has a ferromagnetic order similar to SRO but with a reduced transition temperature of 125 K. The signature of the magnetic order can also be recognized in transport measurement by a kink that is marked with an arrow in Figure 1c. It is evident that there exists an additional anomaly in the resistance data around 260 K. It has been reported that subtle changes in the spin state of BFO, such as a spin reorientation transition, may arise between 10 K and 300 K [20][21][22]. Because BFO is insulating while SRO is metallic, the transport property should be dominated by the SRO layer.…”
Section: Electric and Magnetic Propertiesmentioning
confidence: 99%
“…It should be noted that at present, there is no consensus in the literature on what exactly happens to bismuth ferrite at low temperatures: transformation into a spin glass, 43 spin-orientation transition, 44 or surface transition. 45 Using the model from ref. 46, we determined the anharmonicity parameter values for all the samples:…”
Section: Resultsmentioning
confidence: 99%